Are bankruptcy models adequate for condition assessment of companies listed on Warsaw Stock Exchange - Monika Bolek; Agata Gniadkowska-Szymańska (Financial Internet Quarterly, 2022)
The goal of this paper is to present early warning models used in the process of bankruptcy recognition that should meet the terms of good economic condition. Economic condition of a company on a capital market is good when the goal of the business is achieved, namely the increase in value, that occurs with the increase in earnings per share. The results show that the higher scores in a discriminant model, the lower the EPS growth rate. Correlation and linear regression models are applied on a group of observations from companies listed on Warsaw Stock Exchange.
Keywords: M2; G30; G32; G33; 330; growth of companies; bankruptcy; economic condition